Concrete Materials and Technology A Practical Guide - Janamian, Kambiz; Aguiar, Jose B. (CRC Press/Taylor & Francis Group, 2024)
The design and implementation of high-quality concrete demand an underlying knowledge of concrete fundamentals as well as its constituent materials, and in various formulations. Starting with the basics, Concrete Materials and Technology: A Practical Guide examines the production and chemistry of cement, as well as the different types and their applications. Quality control processes and numerous methods for testing are presented and explained in detail. This book presents the fundamentals of concrete technology and serves as a useful guide for civil engineering students, project managers, concrete quality control managers, and technicians.